Artificial macropores improve maize performance at the seedling stage under poor aeration - Xiong, Peng; Jiang, Fahui; Wang, Yuekai; Zhang, Zhongbin (Frontiers in Plant Science, 2024)
Maize is susceptible to hypoxia stress in soils with poor aeration, but the macropores have the potential to improve soil aeration. We studied the impact of artificial macropores on maize performance under poor aeration. Three levels of air-filled porosity (5%, 10% and 15%) were established, and soil columns with (28 vertical artificial macropores with 0.5 mm diameter) or without macropores were created for each level of air-filled porosity with a bulk density of 1.3 g cm -3 . Root-macropore interactions were visualized using CT scanning (41 µm in resolution). Our results showed that root length density and root biomass significantly increased by 114% and 69%, respectively, as air-filled porosity increased from 5% to 15%. However, when artificial macropores were present, an increase in air-filled porosity had no significant effect on root length densitytraits. The treatment of 5% air-filled porosity with macropores significantly increased root length density and root biomass by 108% and 65%, respectively, relative to the treatment of 5% air-filled porosity without macropores, whereas there was no significant difference in root growth between the treatments of 15% air-filled porosity with and without macropores. Compared to the treatment of 5% air-filled porosity with macropores, there was a significant reduction of 49% in the number of macropores colonized by roots under the treatment of 15% air-filled porosity with macropores. Our results demonstrate that macropores provide preferential paths for the colonization of maize roots, thereby promoting root growth under poor aeration.Creating macropores with bio-tillage can serve as a crucial strategy for enhancing crop performance in poorly aerated soils.